PENGARUH KUALITAS LAYANAN, KEPERCAYAAN DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA TERHADAP NIAT BELI ULANG (Studi Kasus Pada Pizza Hut Setiabudi Semarang). - Ma’ruful Mahbub, 14.05.51.0180 (Students' Journal of Economic and Management, 2018)
This study aims to analyze the effect of service quality, trust, and brand image on customer satisfaction and the impact of Pizza Hut Semarang repurchase intention. The sample in this study were Pizza Hut Semarang customers as many as 100 people. The sampling technique was purposive sampling. The sample criteria used in this study are Pizza Hut Semarang customers, at least 17 years of age, and have made purchases 3 times in the last 3 months. Data collection method in this study is using a questionnaire filled by respondents, namely Pizza Hut Semarang customers. The analysis used in this study includes factor analysis to test the validity, Cronbach alpha formula to test the reliability of the instrument, regression analysis to test the effect of the partial effect of each independent variable tested with the determination coefficient and model fit test to test and prove the effect partially each independent variable. The results of the analysis can be concluded that: Service Quality has a significant positive effect on customer satisfaction Pizza Hut Semarang. Trust has a significant positive effect on customer satisfaction Pizza Hut Semarang. Brand image negatively influence insignificant to Customer Satisfaction Pizza Hut Semarang. Customer Satisfaction has no significant positive effect on the intention to buy back Pizza Hut Semarang Keywords: Service Quality, Trust, Brand Image, Customer Satisfaction and Retaliation Purposes